THE BIOLOGICAL STUDY ON Dolycoris baccarum (Linnaeus) (Heteroptera: Pentatomidae) IN ERBIL –KURDISTAN REGION-IRAQ - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Observations on the biology of Dolycoris baccarum (Linnaeus)were made under  room temperature conditions (26 ± 2°C; 35 ± 10% Relative Humidity) feeding stages were fed on wheat leaves and shelled Sunflower seeds. Light and dark morphs were observed for second, third, fourth and fifth instars; short fine hairs on dorsal head, thorax and abdominal of fourth and fifth instars observed; fifth instars have black and white banded antennae. The mean periods of pre-oviposition, oviposition and post-oviposition were 7.8, 33 and 2.5 days, respectively; the averages of female and male longevity were 43.3 and 36 day respectively, and mean fecundity was 102.4 eggs per female. The barrel eggs usually deposited in masses, the mean number of egg masses and the eggs per masses were 7.2 and 14.4, respectively, the mean incubation period was 7.5days, and egg hatching percentage reached to 68.410%. An average duration of the immature stages (egg to 5th instar) was 42.5 days, and the highest mortality observed in fifth instar (40.1%).